DESIGNING PUBLIC-PRIVATE PARTNERSHIP FOR BONTANG INDUSTRIAL ESTATE - Adjie Pamungkas; Yudha Ardian; Tony Hanoraga; Mohammad Sodiq; M Muhktasor; Vely Kukinul Siswanto (Diponegoro University, 2015)
Bontang Local Government has planned Bontang Industrial Estate (BIE) to accommodate oil, gas, condensate and other industries. The estate will need investment for about IDR. 2.27 Trillion while the total annual local government budget is near to IDR 2 Trillion. Moreover, the estate has to be operated in a business manner while the local government officers have a culture in non-profit organisation as part of bureaucracy. However, the BIE feasibility study 2013 has determined that the estate will generate economic multipliers boosting the city development. Therefore, a partnership among government and private parties should be determined and accommodated in a proper cooperation arrangement. To design the partnership, we review literature, interview related private parties and confirm opinions of the private parties to the governments. A content analysis was used to assess information from the interviews. Considering the final outputs, BIE should be organised by a pure private enterprise or Ltd. to ensure the economic viable of the estate. The Ltd. is a partnership among the government and private parties via shareholders. The government can still hold a majority share with special arrangement in investment scheme. For the initial investments, the government can use its assets valued as 51% of total share while private parties can inject cash money equal to 49% of the total. With this capital arrangement, the estate can be operated with initial investment for about IDR. 267.11 Billion on 244.97 Ha land. This initial investment can be profitable with IDR. 650 Billion NPV, 19.93% IRR and 13.95 year PP.Bontang Local Government has planned Bontang Industrial Estate (BIE) to accommodate oil, gas, condensate and other industries.